Viscosity and Density study of Caffe ine Citrate in Aqueous Solution at 298.15, 303.15 and 308.15 K - Habeeb, Sana A (Al-Nahrain Journal of Science, 2018)
Densities (ρ) and viscosities (η) of caffeine citrate at different temperature (298.15, 303.15, 308.15) K have been measured from these experimental data, The apparent molar volumes ( ) and limiting partial molar volumes ( ), slope ( ), Gibbs free energy of activation for viscous flow of solution and Jones-Doles A and B Coefficients were calculated, The results shows a strong ion- ion interactions and weak ion-solvent interactions and also indicate that caffeine citrate acts as structures maker in aqueous solution.